Density functional theory calculations for evaluation of phosphorene as a potential anode material for magnesium batteries. Issue 13 (13th February 2018) - Han, Xinpeng; Liu, Cheng; Sun, Jie; Sendek, Austin D.; Yang, Wensheng
Abstract : Phosphorene adsorbs Mg to form a stable product MgP2, delivering a theoretical specific capacity of 865 mA h g −1 . Abstract : We have systematically investigated black phosphorus and its derivative – a novel 2D nanomaterial, phosphorene – as an anode material for magnesium-ion batteries. We first performed Density Functional Theory (DFT) simulations to calculate the Mg adsorption energy, specific capacity, and diffusion barriers on monolayer phosphorene. Using these results, we evaluated the main trends in binding energy and voltage as a function of Mg concentration. Our studies revealed the following findings: (1) Mg bonds strongly with the phosphorus atoms and exists in the cationic state; (2) Mg diffusion on phosphorene is fast and anisotropic with an energy barrier of only 0.09 eV along the zigzag direction; (3) the theoretical specific capacity is 865 mA h g −1 with an average voltage of 0.833 V ( vs. Mg/Mg 2+ ), ideal for use as an anode. Given these results, we conclude that phosphorene is a very promising anode material for Mg-ion batteries. We then expand our simulations to the case of bulk black phosphorus, where we again find favorable binding energies. We also find that bulk black phosphorous must overcome a structural stress of 0.062 eV per atom due to a volumetric expansion of 33% during magnesiation. We found that the decrease in particle size is good to increase its specific capacity.